Delivering Interventions Via Telehealth: Functional Communication Training with a Child with Autism as a Case Example. (March 2021) - O'Brien, Matthew J.; Schieltz, Kelly M.; Berg, Wendy K.; McComas, Jennifer J.; Wacker, David P.
In this article, we provide a case example of how telehealth can be used by care providers in their homes to access empirically validated procedures such as functional communication training. As shown in the case example, complex assessment and intervention procedures were implemented successfully by care providers in their homes while receiving real-time coaching by behavior analysts who were located in a hospital in a different city. This case example is representative of the results we obtained thus far; substantial improvements in challenging and adaptive behavior occurred. Given these results obtained to date with telehealth, in terms of both outcomes of interventions and rated acceptability of the procedures by care providers, further and more widespread application of telehealth is warranted.